Prevalencia de caries dental y estilos de vida de niños entre 3-5 años de dos instituciones educativas de las comunas 3 y 7 de Ibagué 2019 (2020)
It is important to know what is the prevalence and severity of caries in children between 3 and 5 years of age, to contribute with the necessary elements in planning educational interventions that favor the development of oral health. Prevention is the most important factor in modern dentistry, since knowledge of risk factors, methods of promotion and oral prevention must be applied in dental patients, in order to improve oral health status.